Material management: bba, 4th semester, wbut - Chopra, Amit (Kalyani Publishers, 2011)
Material management: bba, 4th semester, wbut / Chopra, Amit. -- Kolkata: Kalyani Publishers, 2011 658.7 C549 No. of Copies : 1